The baseline pattern and age-related developmental metabolic changes in the brain of children with autism as measured on positron emission tomography/computed tomography scan - Sharma, Alok; Gokulchandran, Nandini; Sane, Hemangi; Nivins, Samson; Paranjape, Amruta; Badhe, Prerna (World Journal of Nuclear Medicine, 2018)
[18F] 2-fluoro-2-deoxy-D-glucose positron emission tomography-computed tomography scan was performed on 45 children with autism to study the baseline pattern and age-related developmental changes in the brain metabolism. Median standardized uptake values (SUVs) were compared with published healthy control data. Results showed that, in contrary to control data, the median SUVs in children with autism decrease linearly with increase in age. As compared to controls, autism children below 5 years showed greater metabolism and older children showed lower metabolism. In autism group, comparison of absolute SUVs within different regions of the brain revealed relatively lower metabolism in amygdala, hippocampus, parahippocampal gyrus, caudate nucleus, cerebellum, mesial temporal lobe, thalamus, superior and middle temporal pole, and higher metabolic uptake in calcarine fissure and Heschl's gyrus. These results help in understanding the baseline metabolism and developmental changes of brain among different age groups in autism.
Keywords: [18F] 2-fluoro-2-deoxy-D-glucose; autism; brain development; brain glucose metabolism; computed tomography; positron emission tomography